Exploring the different cognitive, emotional and imaginative experiences of autistic and non-autistic adult readers when contemplating serious literature as compared to non-fiction - Chapple, Melissa; Davis, Philip; Billington, Josie; Corcoran, Rhiannon (Frontiers in Psychology, 2023)
Recent research has demonstrated how reflections on serious literature can challenge dominant social-deficit views of autism. This method enables autistic readers to explore social realities more slowly and carefully, encouraging detail-focused considerations. Previous research has also shown that autistic and non-autistic readers reflecting on serious literature together are able to achieve mutuality in a way that enables them to overcome the double empathy problem. However, the advantages of reading aloud designs have yet to be explored with autistic and non-autistic readers due to previous concerns amongst autistic people on the issue of being read aloud to. The present study aimed to explore how an adapted shared reading design that compared serious literature and non-fiction would enable autistic and non-autistic readers to imaginatively engage in the reading experience. Specifically, seven autistic and six non-autistic participants read 8 short text extracts alone while listening to pre-recorded audio of an experienced reader reading each text aloud. Participants completed a reflective questionnaire for each text and a follow-up interview where moving parts of the text were then re-read aloud before discussion. Half of these texts were serious literature, while the other half were non-fiction. Similarly, half of the texts explored fictional social realities that depicted a lack of mutuality, or non-fiction accounts of autism; while the other half explored broader emotional experiences. Thematic and literary analysis of participant reflections and follow-up interviews revealed three main themes: (1) From Surface Reading to Intuitive Engagement, (2) Imaginative Feeling and (3) Going Forward from the Reading Experience. The findings showed that autistic readers were better able to hold onto the detailed complexity of serious literature, while non-autistic readers tended to reduce information down to key ideas and understandings for later generalisation. Findings are discussed in relation to future shared reading designs.